The Moderating Role of Gender in the Relationship Between Teacher Competence, Learning Satisfaction, and Students' Intrinsic Motivation - Maryono Maryono; Dede Dwi Kurniasih; Muhammad Hafidz Khusnadin; Samsuddin Samsuddin; Siswanto Siswanto; Roma Wijaya (Yayasan Keluarga Guru Mandiri, 2025)
Teacher competence is a key factor in creating an effective learning experience in the educational environment, especially in Indonesia's secondary education context. There is still a gap in understanding the role of learning satisfaction as a mediator in the relationship. This study explores the relationship between teacher competence, student learning satisfaction, and students' intrinsic motivation at the secondary education level. This study explores the relationship between teacher competence, student learning satisfaction, and students' intrinsic motivation at the secondary education level. Using the Structural Equation Modeling (SEM) approach, data was analyzed from 100 students to identify the impact of teacher competence on learning satisfaction and intrinsic motivation. The results showed that teacher competence significantly had a positive effect on student learning satisfaction with a pathway coefficient of 0.809 (p 0.01) and had a positive impact on students' intrinsic motivation with a coefficient of 0.345 (p 0.05). In addition, learning satisfaction was proven to have a significant mediating role in the relationship between teacher competence and intrinsic motivation, with a pathway coefficient of 0.493 (p 0.01). These findings support the importance of teacher competency development in improving a satisfying and motivating learning experience for students. This research has practical implications for educational institutions in strengthening teacher training programs and strategies to improve teaching quality to support the overall academic development of students.